2021
DOI: 10.1038/s41598-021-90005-z
|View full text |Cite
|
Sign up to set email alerts
|

MMP20-generated amelogenin cleavage products prevent formation of fan-shaped enamel malformations

Abstract: Dental enamel forms extracellularly as thin ribbons of amorphous calcium phosphate (ACP) that initiate on dentin mineral in close proximity to the ameloblast distal membrane. Secreted proteins are critical for this process. Enam−/− and Ambn−/− mice fail to form enamel. We characterize enamel ribbon formation in wild-type (WT), Amelx−/− and Mmp20−/− mouse mandibular incisors using focused ion beam scanning electron microscopy (FIB-SEM) in inverted backscatter mode. In Amelx−/− mice, initial enamel mineral ribbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Bartlett et al [ 21 ] showed that the knockout of Amelx and Mmp20 in mice resulted in the presence of “fan-like” crystal arrangements in the deeper enamel (20 m of enamel, close to the DEJ), while the middle and outer enamel of such animals show a dysplastic and more mineralized layer [ 21 ]. Interestingly, the enamel of the extant alligator exhibited mineral structures that resemble fans in form ( Figure 5 F–G), with the same orientation (the larger border of the fan towards the outside of the enamel).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bartlett et al [ 21 ] showed that the knockout of Amelx and Mmp20 in mice resulted in the presence of “fan-like” crystal arrangements in the deeper enamel (20 m of enamel, close to the DEJ), while the middle and outer enamel of such animals show a dysplastic and more mineralized layer [ 21 ]. Interestingly, the enamel of the extant alligator exhibited mineral structures that resemble fans in form ( Figure 5 F–G), with the same orientation (the larger border of the fan towards the outside of the enamel).…”
Section: Discussionmentioning
confidence: 99%
“…To date, information on the association of morphological features of dental enamel with the composition (quantity and diversity) of proteins in forming enamel is still poorly understood. In recent years, this information has been obtained primarily from mouse models [ 18 , 19 , 20 , 21 ]. Little is known about other species, since the protein information is gained while enamel is forming, and this usually happens in early life.…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree that ENAM plays vital roles in mineral ribbon formation in both sarcopterygians and actinopterygians but do not necessarily support such roles for AMBN. Furthermore, SCPP5 resembles AMEL (Kawasaki et al, 2021) that is not important for the initial formation of mineral ribbons (Bartlett et al, 2021; Hu et al, 2016; Smith et al, 2016). It is thus likely that the evolution of ENAM was the crucial event for the origin of the unique mineralization process of the enamel matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Charging on the surfaces of block faces was reduced by coating them with a thin layer of platinum (3 nm) where required. Curtaining defects in TLD images were reduced using python language software described previously 85 . In an attempt to better define the DEJ area in Acp4 R110C/R110C mutant mice, images from Acp4 +/+ and Acp4 R110C/R110C mice at sequential levels of section across the first half of the secretory stage were normalized in ImageJ ( https://imagej.nih.gov/ij/ ) based on mean dentin intensity and then pseudocolored using the built in 16 color lookup table (LUT) (Fig.…”
Section: Methodsmentioning
confidence: 99%